2005
DOI: 10.1007/s10238-005-0082-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-1B and interleukin-1RN polymorphisms with gastric cancer in a high-risk population of Costa Rica

Abstract: Several risk factors have been associated with gastric cancer, among them Helicobacter pylori infection. This bacterium yields inflammation, the degree of which depends on the bacterial strain and the severity of the host response. The inflammatory response involves a complex cytokine network. Recently, polymorphisms of the genes coding for interleukin-1beta (IL-1B), interleukin-1Ra (ILRN) and interleukin-10 have been associated with an increased risk of gastric cancer. In order to determine the association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 38 publications
1
55
1
5
Order By: Relevance
“…Of the remaining 38 publications, three were eliminated, due to reporting duplicate data 17, 18, 19. Ultimately, 37 studies from 35 publications 6, 10, 14, 15, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 including 6108 cases and 8980 controls were included in the meta‐analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 38 publications, three were eliminated, due to reporting duplicate data 17, 18, 19. Ultimately, 37 studies from 35 publications 6, 10, 14, 15, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 including 6108 cases and 8980 controls were included in the meta‐analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Since the year 2002, a lot of studies have focused on the IL-10-1082 G allele association with the susceptibility to gastric cancer, but with mixed or conflicting results (Wu et al, 2002;El-Omar et al, 2003;Wu et al, 2003;Savage et al, 2004;Alpízar-Alpízar et al, 2005;Guo et al, 2005;Lee et al, 2005;Lu et al, 2005;Zambon et al, 2005;Kamangar et al, 2006;Morgan et al, 2006;García-González et al, 2007;Sugimoto et al, 2007;Bai et al, 2008;Crusius et al, 2008;Deng et al, 2008;Zhou, et al, 2008a;Kang et al, 2009;Ko et al, 2009;Xiao et al, 2009;Liu et al, 2011;Zhou et al, 2011). Up to now, there has been just one relevant published meta-analysis regarding IL-10-1082 A/G SNP (Zhou et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…The control group consisted of dyspeptic patients of which a large majority suffered from some inflammatory condition (NAG). In a previous study, performed by our group, among participants in a program at the Center for Early Detection of Gastric Cancer in Costa Rica, it was found that IL-1B + 3945T and IL-1RN*2 were associated with an increased risk of gastric cancer: OR = 3.7 P = 0.007 and OR = 2.9; P = 0.03 respectively [34] . In this study, the control groups were normal individuals as judged by X-ray (double contrast, gastric study).…”
Section: Discussionmentioning
confidence: 84%